Redesign of Sago Tempe Chips Packaging Using a Kansei Engineering Approach - Audia, Farhana; Johan, Vonny Setiaries; Juarsa, Rahmadini Payla; Dewi, Yossie Kharisma; Kurniawan, Mhd Andry (Teknotan: Jurnal Industri Teknologi Pertanian, 2026)
Sago tempe chips are snacks made from soybeans and sago flour. The packaging of sago tempe chips uses transparent plastic with label stickers, making it appear simple and less attractive to consumers. One strategy to attract consumers is redesigning the packaging using the kansei engineering approach. This study aims to produce a packaging design for sago tempe chips that suits consumer preferences using a kansei engineering approach. This study helps produce packaging designs that suit consumer desires and needs so that they can attract consumers. The method used is a survey with a kansei engineering approach. Based on this study, eight kansei words were identified, namely informative, unique, artistic, attractive, quality, easy to use, innovative, and colorful. The packaging design concepts extracted from the kansei words using principal component analysis (PCA) were identified as “informative,” “colorful,” and “quality.” The design elements identified from the 10 packaging samples included shape, supporting images, materials, color, and size. Based on the R-squared value of quantification theory type 1 (QTT1), the concept of “quality” was selected because it had a higher value. Tempe sagu chip packaging is considered quality if it has a pillow-shaped bag design, features product images, uses aluminum foil material, employs multiple colors (>3 colors), and has a medium-sized package.